Experience in Using a Set of Current Efferent Methods in the Treatment of Patients with Infectious Pancreonecrosis - R. A. Mlinnik; S. A. Tezyaeva; M. A. Sidorov (Общая реаниматология, 2011)
Objective: to study the effectiveness and safety of an automatic ventilator weaning system in patients with acute respiratory distress syndrome (ARDS) on continuous mechanical ventilation (MV). Subjects and methods. Twenty-eight patients diagnosed as having severe concomitant injury were examined. Due to the evolved ARDS, all the patients were on continuous MV. The study group patients (n=10) were transited to spontaneous breathing through a Smart Care® ventilation system; the control group patients (n=18) were weaned from the ventilator under the control of a resuscitation specialist. Account was taken of the duration of ventilation in the Smart Care® mode and that of patient weaning under the control of a resuscitation specialist, and the need for reintubation, as well as postintubation complications. Results. The application of the automatic ventilator weaning mode showed a 1.3-fold reduction in the length of stay in the patients with severe ARDS under assisted ventilation. Key words: respiratory distress syndrome, mechanical ventilation, ventilator weaning.